The Effectiveness of Doing Online Reading Assignments from Home during Social Distancing Period - Audria Bella Alifva (Universitas Serambi Mekkah, 2021)
This study aimed to find out students’ perceptions about the effectiveness of doing online reading assignments from home during social distancing period.The study used the mixed-method design. Purposive sampling was also used to find out the information related to the students’ perception and experiences of doing online reading assignments. The results showed that 94% of participants perceived online reading assignments as effective. Based on the results, it can be concluded that doing online reading assignments from home during the Corona virus pandemic brings a positive impact to the first- and third- semester students of the English Department at Serambi Mekkah University. Future research on this area is suggested to focus on a different department and level of study.